Ex-ante reminders: The effect of messaging strategies on reducing non-sustainable consumption behaviors in access-based services - Fu, Xiaorong; Xu, Yang (Frontiers in Psychology, 2022)
Users’ non-sustainable consumption behaviors are affecting the sustainability of access-based services (ABSs), but ABS firms can utilize messaging strategies (ex-ante reminders) to persuade users to curtail their non-sustainable consumption behaviors. Through two online scenario-based experiments in China, this study determined that: (1) Compared with rational appeal messaging, emotional appeal messaging is better able to persuade consumers to curtail non-sustainable consumption behaviors. Furthermore, loss-framed messages are more effective than gain-framed ones. (2) Message appeal and message framing have an interactive persuasive effect on reducing such consumer behaviors. Loss-framed rational appeal messages are more persuasive at reducing non-sustainable consumption behaviors than gain-framed rational appeal messages, and gain-framed emotional appeal messages persuade consumers to reduce non-sustainable consumption behaviors more than loss-framed ones. (3) Consumers’ psychological ownership moderates the persuasive effect of messaging. Among consumers with a high level of psychological ownership of shared goods, only gain-framed emotional appeal messaging is effective at reducing non-sustainable consumption behaviors, whereas among consumers with low psychological ownership, the persuasive effect of loss-framed rational appeal messaging is more effective than gain-framed emotional appeal messaging. This study extends the research on non-sustainable consumption behavior management in ABSs and provides important inspiration for the management of ABSs consumer behavior.